Perforated Transverse Vaginal Septum with Primary Infertility: A Case Report - Adhikari, Shree Prasad (Journal of College of Medical Sciences-Nepal, 2023)
Introduction A transverse vaginal septum develops when the canalization of the vaginal plate fails at the intersection of the mullerian duct and the urogenital sinus and It is a rare genital abnormalities in women, with an estimated incidence of 1/70,000 females. Patient with transverse vaginal septum may present with primary amenorrhea, cyclical abdominal pain, haematocolpos, haematometra and infertility. Women with perforated septa may menstruate but have trouble during intercourse. The diagnosis is typically made by a clinical examination together with ultrasound and MRI used for confirmation. We report a case of 24 years female presented with infertility for 5 years diagnosed with perforated transverse vaginal septum managed with resection of septum by hysteroscopy and laparoscopy.